Triangles in the suborbital graphs of the normalizer of $Γ_0(N)$ - Nazlı Yazıcı Gözütok; Bahadır Özgür Güler (Indonesian Journal of Combinatorics, 2020)
In this paper, we investigate a suborbital graph for the normalizer of Γ0(N) ∈ PSL(2;R), where N will be of the form 24p2 such that p > 3 is a prime number. Then we give edge and circuit conditions on graphs arising from the non-transitive action of the normalizer.